THE ROLE OF STUDENT WELL-BEING IN THE SUCCESS OF PHYSICS LEARNING: A LITERATURE REVIEW - Adi Setiawan; Sukarmin; Yulianto Agung Rezeki (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2026)
Student well-being plays a crucial role in academic success, particularly in challenging subjects such as physics. It encompasses school-related, social, emotional, and academic aspects that interrelate to foster an optimal learning experience. This study aims to investigate the relationship between student well-being and achievement in physics learning while offering insights for educators to develop a supportive learning environment that enhances student well-being. The method employed in this article is a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol. Data were gathered from articles published over the past six years, sourced from the Scopus database. The findings indicate that supportive learning environments, such as classrooms and laboratories, indirectly influence physics learning outcomes. Emotional well-being, including the ability to manage stress and maintain intrinsic motivation, directly impacts student engagement in physics education. Furthermore, social support from teachers and peers significantly contributes to boosting students' self-confidence. This research confirms that student well-being not only affects academic success but also fosters essential social and emotional skills.